Processo de alimentação do Sistema de Informação do HiperDia: Estudo de Caso no município de Natal/RN - Sena, Viviane Lima de (2008)
Although the records indicate the involvement of the City Christmas in the feeding system HiperDia, a survey conducted by the Health Ministry in 2004 found that the number of entries made in Natal was well below estimate. In order to understand the functioning of HiperDia, we performed this study to analyze the actions taken by the professionals involved in power system HiperDia in Natal / RN. The research has developed into a quantitative perspective, with the design of exploratory case study conducted in the health services that integrate the various levels of the organization who are directly involved with the process of system power HiperDia in Natal / RN , represented here by SMS, health districts and the Family Health Units in the period from August to October 2008.Study participants were 110 professionals, including nurses, physicians, operators, administrator and a coordinator. The survey results showed that feeding HiperDia in Natal was maintained mainly by health professionals and operators. Activities include carrying out the state registration, monitoring, and updating of data transfer routines. They report that the difficulties in the process of feeding data are related to the work of teams and / or lack of structure of the Program of Hypertension and Diabetes (HA and DM), the discontinuity of federal investments in improving the HiperDia and lack of training. We can see then that the process of feeding system on Christmas HiperDia therefore is developing the three levels (SMS, districts and health units), however is not matching the expectations established by MS, considering that the gaps the flow of information are undermining the end result of this process